Penggunaan Mikroorganisme Akuatik pada Proses Nitrifikasi di Tambak Udang (Litopeneaus vannamei) - Septriono, Wahyu Adi; Indrian, Friska; Khairunnisa, Siti; Gultom, Ester Romatua (MAIYAH, 2023)
Vaname shrimp is one of the potential cultivation commodities to be developed, because it has quite high economic value and has become an export commodity. In shrimp farming activities, feed is inseparable, where feed is the main factor in aquaculture production. The feed used has a high protein content, but only 75% can be used as feed and the rest will settle on the aquaculture pond substrate. The remaining feed that settles will be toxic and even cause death to cultivated biota because it contains ammonia. The nitrification process is a process that can convert ammonia compounds into nitrites to overcome cultivation problems. Some microorganisms that can be utilized in the nitrification process are:Nitrosomonas, Nitrosococcus, Nitrospira, Nitrosolobus, andNitrosovibrio. One of the commercial probiotics uses a dose of 0.1 - 0.2 ppm 1-2 times in a span of one week, sprinkled evenly on the pond by aeration first because the product is in powder form. Dosage can be increased or decreased according to shrimp and environmental conditions.